FINANCIAL MANAGEMENT ACCOUNTABILITY AND TRANSPARENCY ASSISTANCE THROUGH FINANCIAL REPORT AUDITS AT SD MUHAMMADIYAH SEMBORO JEMBER - Suharsono, Riyanto Setiawan; Muhibbin, Maulana Arif; Halim, Moh; Thamrin, Mohamad (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
The reforms taking place in Indonesia have resulted in the emergence of a democratic spirit, accountability and transparency in the government sector. Reforms in various fields have led to the realization of the implementation of the duties and functions of state governance and development characterized by the principles of good governance. In implementing education, schools have autonomy. This educational autonomy model is School Based Management (SBM). Schools have the authority to carry out creativity, innovation and improvisation in realizing quality education. The School-Based Management (SBM) concept makes education management more focused and well-coordinated in terms of implementation, funding, development and supervision. This Community Service Program seeks to provide answers and solutions to problems to create accountability and transparency in financial management in public institutions at the central and regional levels, including schools. Based on the problems faced by the community, the service that will be carried out is to provide training and education to the school, especially the Principal, Treasurer and Financial Executive at SD Muhammadiyah Semboro Jember. This community service method uses seminars/workshops, practice and discussions with the Principal, Treasurer and Financial Executive at SD Muhammadiyah Semboro Jember